Helminthes in Amphibians from Pu Mat national park, Nghe An province - Ngo, Ha Duy; Ngai, Do Duc; Ha, Nguyen Van; Duc, Nguyen Van (Academia Journal of Biology, 2012)
168 Amphibians of 5 species (Rana ragulosa, Rana guentheri, Bufo melanostictus, Rana limnocharis and Polypedates mutus) from Pu Mat national park, Nghe An province were examined for Helminthes study. The result indicated that the average infection rat of Helminthes was at 80.36%, among them Cetoda 17.86%, Trematoda 15.48%, Nematoda 69.05%) and Acanthocephalan 8.93%. 11 Helminthes species collected from these studied Amphibians were identified, 1 species (Pseudoacanthocephalus caucasius) of Acanthocephalan, 3 species (Cosmocerca omata, Oswaldocruzia hoeppli and Rhabdias bufonis) of Nematoda and 7 species (Brachycoelium salamandrae, Diplodiscus amphichrus, Ganeo glotoides, Glythelmins rugocaudata, Ninemandijia kashmirensis, Mesocoelium peasei and Pleurogenoides sphaericus) of Trematoda.